Sistematização da assistência de enfermagem na ótica de enfermeiros de unidades de terapia intensiva - Abrantes, Rogéria Moreira de (2010)
Introduction: Nursing Care Systematization is the method that enables the implementation of the nursing process. Even being aware of the importance of the nursing process, many nurses still do not apply in its entirety because of the difficulties encountered with regard to its operation, such as lack of knowledge in the process steps, little skill in physical examination and responsibility towards bureaucratic activities imposed on them. Objective: Study the understanding and the importance of the intensive care units nurses work into the Nursing Care Systematization as a tool of the professional practice. Methodology: a descriptive, exploratory and field with a quantitative approach. It was developed in ICUs of five hospitals in the city of Joao Pessoa. Before the completion of their research project was referred to the Ethics Committee in Research of Hospital Universitário Lauro Wanderley, Federal University of Paraíba, and other institutions where the research was developed. The nurses who agreed to participate in the study signed a consent form. The study consisted of 51 nurses from the ICUs of five hospitals chosen for the research. The sample consisted of 28 nurses who agreed to participate. The data collection instrument was a structured questionnaire with 21 questions of objective and subjective nature. A database was constructed and analyzed by the microcomputer program Statistical Package for Social Science (SPSS), version 8.0. Windows and analyzed using absolute and relative distribution. Results: The study revealed that most participants were aged between 20 and 30 years old were female, with some expertise in health from 01 to 05 years of professional experience and expertise in the ICU, and nurses were welfare. The results showed that the nurses who were participants of the study do not dominate the concept of SAE. They also do not know the phases of the EP and know how to perform them well, though they consider themselves ready for it. When they were asked about the theoretical framework used, most quoted Horta. From receiving training on the NCS, the majority claimed to have received training in the academy in the training period. The doubts about SAE focused on the development of the nursing diagnoses and nursing evolution. When they were asked about the legislation that supports the SAE, the majority claimed to know the resolution that regulates the SAE. Some of the nurses believe that SAE improves nursing care, they were favorable to its implementation and pointed to work overload as a factor that hinders the implementation of PE. In direct patient care, the greatest hindrance is the lack of knowledge and yet this was the justification presented for the effective implementation of PE not in some institutions in the city. Conclusion: We conclude that it is necessary to invest in continuing and continued education to remedy the difficulties pointed out by nurses and eradicate the little knowledge we have about the issue in order to deliver improvements in patient care and giving greater visibility to the profession.